The Contribution to knowledge of the Entomologic Fauna of Mangroves: Olla roatanensis Vandenberg and Cheilomenes sexmaculata Fabricius, two new records of Coleoptera: Coccinellidae for Ecuador and Peru (Revista Científica Ciencias Naturales y Ambientales, 2015)
The lady bugs Olla roatanensis Vandenberg (Coccinellidae, Coleoptera) and Cheilomenes sexmaculata Fabricius are reported for first time from Ecuador and Peru, both Coleoptera: Coccinellidae have been found on mangrove ecosystems. The morphology and behavior of final larval stage, pupe and adult of Olla roatanensis are described.
Keywords: Cheilomenes sexmaculata; Ecuador; mangroves; new records; Olla roatanensis; Peru